2008
DOI: 10.1007/s10681-008-9797-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic stability at nuclear and plastid DNA level in regenerated plants of Solanum species and hybrids

Abstract: In this work we detected the extent of variability at nuclear and cytoplasmic DNA level of regenerated plants belonging to Solanum genotypes with a different genetic background and somatic chromosome number. As for the nuclear characterization, a total of 66 (18.5%) polymorphic bands were scored using 13 ISSR primers on 45 randomly selected regenerants. Our results show that the regenerants obtained from clone cmm 1T and, at lower level, those from cph 1C are unstable under in vitro conditions or rather more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 46 publications
0
19
0
1
Order By: Relevance
“…Dann and Wilson (2011) observed genetic (8.75-15.63 % polymorphisms) and epigenetic (12.56-26.13 % polymorphisms) variations among regenerants of potato derived from long-term nodal tissue culture and cell selection. Aversano et al (2009) demonstrated that under in vitro culture conditions Solanum genotype affects the integrity of the genome and absence of polymorphism at plastid level confirms the greater genetic stability of cytoplasmic DNA. Li et al (2007) demonstrated genetic and epigenetic instabilities induced by tissue culture in wild barley using AFLP, S-SAP and MSAP markers.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Dann and Wilson (2011) observed genetic (8.75-15.63 % polymorphisms) and epigenetic (12.56-26.13 % polymorphisms) variations among regenerants of potato derived from long-term nodal tissue culture and cell selection. Aversano et al (2009) demonstrated that under in vitro culture conditions Solanum genotype affects the integrity of the genome and absence of polymorphism at plastid level confirms the greater genetic stability of cytoplasmic DNA. Li et al (2007) demonstrated genetic and epigenetic instabilities induced by tissue culture in wild barley using AFLP, S-SAP and MSAP markers.…”
Section: Discussionmentioning
confidence: 76%
“…ISSRs use longer primers (15-30 mers) as compared to RAPD primers (10 mers), which permit the subsequent use of high annealing temperature leading to higher stringency. In the past RAPD and ISSR markers have been proven to be quite efficient in detecting genetic fidelity in several plant species such as Prunus dulcis (Martin et al 2004), Solanum species (Aversano et al 2009), Cymbopogon martinii (Bhattacharya et al 2010), Gynura bicolor (Liu et al 2011), Malus domestica (Pathak and Dhawan 2012), Simmondsia chinensis (Kumar et al 2011), Gerbera jamesonii (Bhatia et al 2011) and Lilium orientalis (Liu and Yang 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Micropropagation techniques are of practical importance; many currently published papers on in vitro-induced genetic changes relate to the variability of cloned plants (somaclonal variation). Most of them show a rich array of genetic variants (Bednarek et al, 2007;Jin et al, 2008;de la Puente et al, 2008;Aversano et al, 2009;Mo et al, 2009) though only a small part of the genetic variability is transferred from cultured tissues to micropropagated plants. Genetic variation in vitro arises from chromosome alterations and/or changes on the DNA level (Lee and Phillips, 1988;Kaeppler et al, 2000;Kwasniewska et al, 2012), but it remains unclear whether these phenomena occur independently.…”
Section: Discussionmentioning
confidence: 99%
“…tbr allopolyploids maintained in vitro probably reflected somaclonal variation occurring during protoplast regeneration through the callus dedifferentiating stage. According to Aversano et al (2009), who studied the variability of nuclear and cytoplasmic DNA level in Solanum genotypes with a different genetic background and ploidy (wild species and hybrids, including S. nigrum and a somatic hybrid 4x S. tuberosum ? 2x S. bulbocastanum), the integrity of the nuclear genome of the in vitro regenerants depended on the genotype.…”
Section: Discussionmentioning
confidence: 99%